2006
DOI: 10.1128/cvi.00173-06
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Long-Term Lipopolysaccharide Tolerance by an Agonistic Monoclonal Antibody to the Toll-Like Receptor 4/MD-2 Complex

Abstract: We have established an agonistic monoclonal antibody, UT12, that induces stimulatory signals comparable to those induced by lipopolysaccharide (LPS) through Toll-like receptor 4 and MD-2. UT12 activated nuclear factor B and induced the production of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-␣) and interleukin-6 (IL-6) in peritoneal exudative cells. In addition, mice injected with UT12 rapidly fell into endotoxin shock concomitant with the augmentation of serum TNF-␣ and IL-6 levels, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…While administration of TLR4 ligands directly to the CNS may effectively induce clearance of amyloid (19), in practice this route would be complicated to exploit in humans. The alternative, systemic treatment with these agents by peripheral injection, could lead to lethal side effects induced by high levels of evoked proinflammatory mediators, such as TNF-␣ and IL-1␤ (17,44). The negative consequences of TNF-␣ and IL-1␤ generation, which result from TLR4 activation, might be counteracted without dampening prion infection-protective phagocyte activation by coadministering specific antagonists to neutralize these cytokines (4,27,39).…”
Section: Discussionmentioning
confidence: 99%
“…While administration of TLR4 ligands directly to the CNS may effectively induce clearance of amyloid (19), in practice this route would be complicated to exploit in humans. The alternative, systemic treatment with these agents by peripheral injection, could lead to lethal side effects induced by high levels of evoked proinflammatory mediators, such as TNF-␣ and IL-1␤ (17,44). The negative consequences of TNF-␣ and IL-1␤ generation, which result from TLR4 activation, might be counteracted without dampening prion infection-protective phagocyte activation by coadministering specific antagonists to neutralize these cytokines (4,27,39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that UT12 induces endotoxic shock-like symptoms in mice including augmentation of TNF-α and IL-6. Furthermore, UT12 induced long-term tolerance and protection against LPS-induced lethal shock in mice (14). However, the ability of UT12 to induce translocation of TLR4/MD2 into endosomes, as well as its potential for mediating TRIF-dependent signaling, has not been reported.…”
mentioning
confidence: 98%
“…TLR4 endocytosis and TRIF-mediated signaling were induced by treatment of macrophages with UT12, a mouse antibody directed against an epitope formed by TLR4/MD2 interaction (13,14), and small synthetic TLR4 ligands (1Z105 and 1Z204) that bind to MD2 and signal through both MyD88-dependent and TRIFdependent pathways in the absence of CD14 (16). Although it is possible that the UT12 monoclonal antibody also activates internalization through FcγR-dependent uptake of UT12/TLR4/ MD2 immune complexes, UT12 is a mouse IgG3 that has high affinity for FcRn and very low affinity/no affinity toward FcγRI, FcγRIIB, FcγRIII, and FcγRIV (38,39).…”
Section: Cd14-independent Endocytosis Of Tlr4 In Macrophages Renderedmentioning
confidence: 99%
“…UT12 acts as an agonist of the TLR4/MD-2 complex and induces a stimulatory signal similar to the original ligand LPS (15). UT12 can induce the production of NF-B and inflammatory cytokines involved in the innate immune system from peritoneal exudate cells in vitro (15). Previous studies have demonstrated that prophylactic treatment with TLR ligands enhances host immunity against influenza virus infection or pneumococcal infection alone (16,17).…”
mentioning
confidence: 99%
“…UT12 acts as an agonist of the TLR4/MD-2 complex and induces a stimulatory signal similar to the original ligand LPS (15). UT12 can induce the production of NF-B and inflammatory cytokines involved in the innate immune system from peritoneal exudate cells in vitro (15).…”
mentioning
confidence: 99%